A case study material flow simulation based analysis for maintenance network improvement - Bilge, Pinar; Abdul Rahman, Azrul Azwan (Universiti Teknikal Malaysia Melaka, 2014)
The competitiveness of enterprises operating in complex environments depends on how well their value creation factors can adapt to disruptions caused by unanticipated events. Building this resilience requires the ability to identify uncertainties and to model their impact on operations, which is difficult to achieve. Thus, increasing adaptability in maintenance and repair networks calls for an adequate approach to address uncertainties. It is necessary to consider the maintenance activities within and outside the company as well as those affecting all equipment supplier partners. Enhancement in simulation technique has opened the opportunity to analyse this complex system. This paper presents a comprehensive analysis introducing a potential approach using material flow simulation that models and simulates the impact of existing maintenance and repair activities to identify the uncertainties to increase the flexibility of the network while ensuring profitability and continuity.